Asuhan Kebidanan Komprehensif Pada Ibu Hamil, Bersalin SC, Nifas, Bayi Baru Lahir, KB Pada NY. “W” G1P0A0 Di Puskesmas Maja Tahun 2024 - Aminah; Hilwa Mail Haq (Jurnal Obstretika Scientia, 2024)
Pregnancy, childbirth, postpartum and BBL are physiological things. However, it is not uncommon for the process to have several obstacles in the form of complications. Lebak Regency Health data in 2023, the MMR is 24 people. For IMR, in 2023 there will be a total of 253 cases of infant deaths. Therefore, a solution is needed to reduce this problem, one of which is continuous care (Continuity of Care). The method for writing this Case Study report uses the Varney midwifery management and SOAP. An assessment was carried out at 36 weeks of gestation and a mild anemia problem was found with Hb of 9.9 gr/dL. After anemia management was carried out, at 37 weeks of gestation Hb 10.2 gr/dL. There was a decrease in Hb levels to 9.4 gr/dL at UK 40 weeks before delivery and increased to 10.4 gr/dL after delivery. The mother experienced Oligohydramnios UK 40 weeks need SC procedure. The postpartum period proceeded normally the abdominal scar tissue being dry and clean, and there was lochea rubra at KF 6 hours. Postpartum mothers are given on how to care for wounds, basic needs and oral therapy, namely Vit A 200,000 IU. Tthe introduction of contraceptives at KF 13 days and advised to use implants, but the mother preferred 3-month injectable. When the birth control is 34 days, the mother is advised to take birth control injections for 3 months 42 days after delivery according to the doctor's recommendation. Newborn with normal condition, no abnormalities, BW 2,570 grams, BL 47 cm. Babies are given Vitamin K, eye ointment, Hb 0.5, and exclusive breast milk.